Pre-parliamentary party career and political representation. Issue 6 (18th September 2020) - Binderkrantz, Anne Skorkjær; Nielsen, Marie Kaldahl; Pedersen, Helene Helboe; Tromborg, Mathias Wessel
Abstract: Members of parliament are accountable to both their district and party. Consequently, they have to balance their responsiveness to these competing principals when their preferences diverge. Existing research on this representational dilemma focuses mostly on the role of political institutions, whereas this article offers a new individual-level explanation: pre-parliamentary party careers. Using sequence analysis, three ideal-typical pre-parliamentary career paths are identified: the party local, the party functionary, and the party civilian. The share of party locals increases over time at the expense of party civilians in the Danish parliament, and these party locals are more likely to diverge from the party's position when it is unpopular among their constituents. These findings corroborate existing evidence of political professionalisation in parliamentary democracies, but they also suggest that professionalisation may be associated with a localisation of politics leading to more rather than less constituency representation.